Kondisi Hidrodinamika dan Transpor Sedimen di Perairan Muara Sungai Ayung dengan Simulasi Delft 3D - Putu Indah Dianti Putri; Muhammad Syahril Badri Kusuma (Jurnal Aplikasi Teknik Sipil, 2023)
The morphology of river mouths is influenced by several factors, including waves, river discharge, tides, currents, and those caused by human intervention. This study explores the dynamics of erosion and sedimentation processes in the estuary of the Ayung River caused by lithology, wind, tides, currents, and waves. This study aimed to determine the effect of river discharge, tides, currents, and waves on erosion and sedimentation in the waters of the Ayung River Estuary. Hydrodynamics and sediment transport modeling using Delft 3D software. As a validation of the modeling results, a calibration was performed on the results of hydrodynamic parameter measurements that had been carried out previously. The review conditions are divided into the rainy season (December – March) and the dry season (April – November). River discharge, tides, currents, and waves affect littoral processes on the shoreline around the waters of the Ayung River. This influence causes erosion and sedimentation around the coastal area and affects sediment transport both in the rainy and dry seasons.